2023
DOI: 10.26508/lsa.202302101
|View full text |Cite|
|
Sign up to set email alerts
|

Dispersal of PRC1 condensates disrupts polycomb chromatin domains and loops

Abstract: Polycomb repressive complex 1 (PRC1) strongly influences 3D genome organization, mediating local chromatin compaction and clustering of target loci. Several PRC1 subunits have the capacity to form biomolecular condensates through liquid–liquid phase separation in vitro and when tagged and over-expressed in cells. Here, we use 1,6-hexanediol, which can disrupt liquid-like condensates, to examine the role of endogenous PRC1 biomolecular condensates on local and chromosome-wide clustering of PRC1-bound loci. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
1
0
0
Order By: Relevance
“…Mechanistically, increasing the concentration of PRC2 through CBX2 phase separation facilitates both nucleation and H3K27me3 spreading since a local high concentration can enhance reaction rates. Consistent with this hypothesis, our earlier studies have shown that LLPS speeds up the on-rate of the binding of CBX2 to chromatin 37 , and a recent study has indicated that phase-separated condensates play a role in the clustering of Polycomb target genes 96 . Taken together, these results suggest that sparse CBX2 nucleates PRC1 and PRC2 to assemble Polycomb condensates to create a high local concentration of PRC2 and to cluster Polycomb target genes, which facilitates H3K27me3 deposition and demarcates the spatial boundaries of H3K27me3 domains.…”
Section: Polycomb Target Genessupporting
confidence: 63%
“…Mechanistically, increasing the concentration of PRC2 through CBX2 phase separation facilitates both nucleation and H3K27me3 spreading since a local high concentration can enhance reaction rates. Consistent with this hypothesis, our earlier studies have shown that LLPS speeds up the on-rate of the binding of CBX2 to chromatin 37 , and a recent study has indicated that phase-separated condensates play a role in the clustering of Polycomb target genes 96 . Taken together, these results suggest that sparse CBX2 nucleates PRC1 and PRC2 to assemble Polycomb condensates to create a high local concentration of PRC2 and to cluster Polycomb target genes, which facilitates H3K27me3 deposition and demarcates the spatial boundaries of H3K27me3 domains.…”
Section: Polycomb Target Genessupporting
confidence: 63%
“…As for facultative heterochromatin, several results indicate that chromatin segments inactivated by Polycomb complexes are phase condensates [33,119]. In agreement with this, treatment of cells with 2,6-hexanediol, an agent that destroys liquid-phase condensates, leads to the disintegration of Polycomb bodies [120].…”
Section: The Role Of Physicochemical Processes In the Formation Of A ...mentioning
confidence: 68%